Iluko-English-Tagalog dictionary - Laconsay, Gregorio (Phoenix Pub. House, 1993)
A compilation of Iluko-English-Filipino words, their translations, meanings, syllabications and accents. It aims to bridge communications among Ilocanos living in different regions, as well as introduce Iluko to Filipinos and foreigners alike and the use of the dialect.